Air Force Major Defense Acquisition Program Cost Growth Is Driven by Three Space Programs and the F-35A Fiscal Year 2013 President's Budget Selected Acquisition Reports - Leonard, Robert S. (RAND Corporation, 2014)
Controlling costs in Major Defense Acquisition Programs is essential to the overall affordability of Air Force modernization plans. A handful of ongoing and recently terminated programs account for substantially higher cost growth in recent Air Force programs compared with complete programs. Cost growth to date in four continuing large-dollar programs must be contained to ensure affordability of the Air Force's long-term investment plans.